A Child-Directed Music Curriculum in the Montessori Classroom: Results of a Critical Participatory Action Research Study - Dansereau, Diana R.; Wyman, Brooke (Journal of Montessori Research, 2020)
Maria Montessori strongly advocated for music learning to be fully integrated into the classroom; however, many Montessori classrooms are dominated by materials aimed at developing children’s visual sense. The purpose of this critical participatory action research (CPAR) study was to address this perceived learning disparity by developing and implementing a curriculum that is consistent with the Montessori approach, child directed, and focused on sound examination and music learning. We designed six shelf works and offered them, over the course of 6 CPAR cycles, to 20 3- to 6-year-old children attending a Montessori school. Findings from qualitative and quantitative data indicate that the children received the works positively, chose to engage with them, became more confident in their musical tasks over time, showed signs of deep concentration and attention, and demonstrated consistent performance across similar tasks related to perception and cognition. We conclude that the presence of these 6 curricular works began to disrupt the perceived learning disparity we identified; however, more can be done to understand and change the classroom practices that support that disparity.